Boosting the Electrochemical Performance of PI-5-CA/C-SWCNT Nanohybrid for Sensitive Detection of E. coli O157:H7 From the Real Sample - Wang, Huan; Fan, Yanmiao; Yang, Qiaoli; Sun, Xiaoyu; Liu, Hao; Chen, Wei; Aziz, Ayesha; Wang, Shenqi (Frontiers in Chemistry, 2022)
Redox activity is an important indicator for evaluating electrochemical biosensors. In　this work, we have successfully polymerized indole-5-carboxylic acid into poly5-carboxyindole nanomaterials (PI-5-CA), using its superior redox activity and introducing carboxylated single-walled carbon nanotubes (C-SWCNTs) to synthesize a composite material. Finally, as synthesized composite material was used for the modification of glass carbon electrode to fabricate PI-5-CA/C-SWCNTs/GCE immunosensor and successfully applied for the sensitive detection of E.coli O157:H7. The fabricated immunosensor exhibited outstanding electrocatalytic activity towards the detection of E.coli O157:H7 with remarkably lowest limit of detection (2.5 CFU/mL (LOD=3 SD/k, n=3) with a wide linear range from 2.98×101~2.98×107 CFU/mL. By getting inspiration from the excellent results, the fabricated electrode was applied for the detection of bacteria from real samples (water samples) with a pleasing recovery rate (98.13-107.69%) with an excellent stability and specificity. Owing to its simple preparation, excellent performance and detection time within 30 min, our proposed immunosensor will open a new horizon in different fields for the sensitive detection of bacteria from the real samples.